Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Kompetensi Pedagogik Guru PAI di Era Digital di SMPN 4 Jombang - Vita Rokhmatul Hidayah; M. Aliyul Wafa; Rohmat Hidayat (Lembaga Yasin AlSys, 2026)
Developing the pedagogical competence of Islamic Religious Education (PAI) teachers in the digital era continues to face challenges, particularly in integrating technology into instructional planning, implementation, and evaluation. This situation requires targeted and sustainable human resource management (HRM) strategies to ensure that teachers’ competencies develop in accordance with the demands of digital learning. This study aimed to describe HRM strategies for improving the pedagogical competence of PAI teachers at SMP Negeri 4 Jombang and to identify the supporting and inhibiting factors and efforts to overcome these obstacles. The study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving the principal, PAI teachers, and students as informants. The data were analyzed using the Miles, Huberman, and Saldaña model through data condensation, data display, and conclusion drawing, while data validity was examined through source and technique triangulation. The findings showed that the HRM strategies were implemented through program planning, in-house training (IHT), Musyawarah Guru Mata Pelajaran (MGMP), workshops, technical guidance, the provision of technology-based learning facilities, supervision, and evaluation. The implementation of these strategies was supported by the principal’s commitment, the availability of technological facilities, opportunities for competency development, a culture of collaboration among teachers, and positive responses from students. The main obstacle was scheduling conflicts between competency development activities and teaching duties. This study concludes that planned and sustainable HRM strategies support the strengthening of PAI teachers’ pedagogical competence in addressing the demands of digital learning. These findings imply the importance of continuous teacher professional development supported by school leadership, technological facilities, collaboration, supervision, and evaluation.